Modified Baihu decoction therapeutically remodels gut microbiota to inhibit acute gouty arthritis - Wang, Xianyang; Long, Haishan; Chen, Ming; Zhou, Zongbo; Wu, Qinlin; Xu, Shijie; Li, Geng; Lu, Zhifu (Frontiers in Physiology, 2022)
MBD is a classic herbal (TCM) formulation that has been widely used for thousands of years due to its safety and efficacy in the treatment of AGA. The aim of this study was to induce acute gouty arthritis (AGA) in rats with monocrystalline sodium urate and elucidated the mechanism by which MBD alleviates AGA through pro-inflammatory cytokines in serum and intestinal ecosystem. AGA rats were orally administered MBD (5.84,35g/kg) with DS-tablet as a positive control. The serum biochemical assays indicated that MBD was effective for treating AGA in SD rats, and it was effective in reducing serum levels of UA, IL-1β, TNF-α and TGF-β1, as well as AGA-related symptoms such as foot swelling. The immunohistochemical results also showed that MBD reduced the expression of inflammatory factors such as TNF-α, IL-1β, NLRP3, ASC and Caspase-1 in synovial tissue. Furthermore, compared with control group, the 16s rDNA sequencing of AGA rat faeces revealed an increase in the relative abundance of Lachnospiraceae, Muribaculaceae, and Bifidobacteriaceae species. While the relative abundance of Lactobacillaceae, Erysipelotrichaceae, Ruminococcaceae Prevotellaceae and Enterobacteriaceae showed a relative decrease in species abundance. Of these, the reduction in species abundance of Enterobacteriaceae was associated with a reduction in amino acid metabolism and environmental perception. After MBD therapeutic intervention, the disturbance of the intestinal flora caused by AGA was restored. In summary, MBD is an effective agent for the treatment of AGA, with the potential mechanism being the regulation of intestinal flora to control inflammation. This would help to promote the therapeutic effect of MBD on AGA.